Updated understanding of the outbreak of 2019 novel coronavirus (2019‐nCoV) in Wuhan, China - Wang, Weier (J Med Virol, 2020)
To help health workers and the public recognize and deal with the 2019 novel coronavirus (2019‐nCoV) quickly, effectively, and calmly with an updated understanding. A comprehensive search from Chinese and worldwide official websites and announcements was performed between 1 December 2019 and 9:30 am 26 January 2020 (Beijing time). A latest summary of 2019‐nCoV and the current outbreak was drawn. Up to 24 pm, 25 January 2020, a total of 1975 cases of 2019‐nCoV infection were confirmed in mainland China with a total of 56 deaths having occurred. The latest mortality was approximately 2.84% with a total of 2684 cases still suspected. The China National Health Commission reported the details of the first 17 deaths up to 24 pm, 22 January 2020. The deaths included 13 males and 4 females. The median age of the people who died was 75 (range 48‐89) years. Fever (64.7%) and cough (52.9%) were the most common first symptoms among those who died. The median number of days from the occurence of the first symptom to death was 14.0 (range 6‐41) days, and it tended to be shorter among people aged 70 years or more (11.5 [range 6‐19] days) than those aged less than 70 years (20 [range 10‐41] days; P = .033). The 2019‐nCoV infection is spreading and its incidence is increasing nationwide. The first deaths occurred mostly in elderly people, among whom the disease might progress faster. The public should still be cautious in dealing with the virus and pay more attention to protecting the elderly people from the virus.